The Use of Apostrophes in Theses of English Students at the University of Bengkulu - Rilda Apriananda Arimbi; Zahrida Zahrida; Ildi Kurniawan (Universitas Bengkulu, 2021)
The purposes of this study were to find out the functions of apostrophes used in the students’ theses and to identify the quality of students’ understanding in using apostrophes. The objects of this research were 40 theses of 2015 English students who graduated in 2019. The instruments of this research were documents and a table checklist that were used to find out the functions and errors of apostrophes in introduction, results and discussion chapters. The data were analyzed by using descriptive quantitative method. The results showed that there were five functions of apostrophes including plural possession (65.9%), singular possession (29.1%), contraction (3.9%), separate possession (0.6%), and joint possession (0.5%). In addition, there were four types of errors consisting of possession words without apostrophes (57.1%), apostrophes in the wrong places (37.8%), plural nouns with apostrophes and the letter s (3.8%), and contractions without apostrophes (1.3%). From the calculation, the percentage of all errors was 25% which indicated that the quality of the students’ understanding of the use of apostrophes was at a “high” level. It can be concluded that the students already understands the use of apostrophes well.